MEMANFAATKAN MEDIA SOSIAL SEBAGAI SARANA DAKWAH BAGI AKADEMISI MUSLIM - Ayuwan Nandani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2018)
This paper examines the role of Islamic higher education students in answering the problems of community life, especially in the field of religion. Technological advances have a major impact on the spread of information on social media. In social media in the postmodern era, people are flooded with a variety of information that cannot be guaranteed. So that the active role of Islamic university students is needed to filter information related to religion. In reviewing this, quantitative and qualitative research is carried out by observing, interviewing and documenting studies. This research is devoted to the practice of the field on social media which is used as a place to appreciate da’wah. Social media is in the form of Facebook, Instagram, Twitter, and even communication media like WhatsApp. From this research, the results obtained that social media can be a supporting tool for preaching. This can be used by students of Islamic universities in Indonesia. Especially students majoring in Interpretation to preach in the crowd. In addition, their preaching on social media can be the right reference, namely to answer the daily problems of the people in Indonesia.